ADMET Analysis of Allicin, Capsaicin, Curcumin, and Genistein Compounds as Cancer Drug Candidates - Novyananda Salmasfattah; Fendy Prasetyawan; Yuneka Saristiana (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2026)
Background. Cancer treatment with hormone therapy such as Doxorubicin has been widely practised in breast cancer, bowel cancer, and others. However, sometimes the side effects of hormone therapy appear and worsen the patient's condition. The compounds (test compounds) Allicin, Capsaicin, Curcumin and Genistein have potential as anticancer compounds. The similarity of the medicinal properties of the test compounds with Doxorubicin, allows them to be used as cancer drug candidates. In addition, it is necessary to analyse ADMET to determine the efficacy and safety of the test compounds. Purpose. This study aims to analyse the ADMET of the compounds Allicin, Capsaicin, Curcumin and Genistein. Method. This research uses the in silico method. Test compounds; Allicin (PubCHem CID 65036), Capsaicin (PubChem CID 1548943), Curcumin (PubChem CID 969516), Genistein (PubChem CID 5280961) and Doxorubicin (PubChem CID 31703) as positive controls were obtained from PubChem. Analysis of test compounds using the PASS online programme to determine the binding activity of compounds with proteins. To determine absorption, distribution, metabolism, excretion, and toxicity (ADMET) using pkCSM online. DruLiTo was used to analyse the physico-chemical properties of the test compounds. Results. Allicin has good ADMET with Intestinal absorption 96.229 (%absorbed), BBB permeability 0.506 (log BB), Total Clearance 0.704 (log ml/min/kg), and does not cause hepatotoxicity. Conclusion. It can be concluded that all test compounds have their own advantages and disadvantages, but Allicin has better ADMET than other test compounds. Further research on Molecular Dynamics needs to be done to find out the interaction of test compounds with Caspase-3 Protein.